Process and material as biographical content: Notions of self-generating sculpture in selected artworks by Tara Donovan - Nitegeka, Ansie (My University, 2014)
This dissertation brings together a practical and theoretical component through a written practice led examination of the concepts that define an artistic practice. Specifically by looking at the Sublime and how it manifests itself within the work of the artists Tara Donovan, Ives Klein and Ansie Nitegeka. The biography of the material is traced using Richards Bay and the key idea of the dolos as a liminal marker, and its relationship to space, to trace the material impacts on artistic process. The material impacts are extended using selected works from the artists and their ways of making and connecting them to the concepts of the Sublime, material, emptiness/Nothingness/Void and the Self-‐generating system. Resulting in works that are made from materials that are traditionally inadequate. Concluding that through the access point of the potential space something can be made from nothing.